Genetic regulation of flowering time and inflorescence architecture by MtFDa and MtFTa1 in Medicago truncatula. Issue 1 (17th November 2020) - Cheng, Xiaofei; Li, Guifen; Krom, Nick; Tang, Yuhong; Wen, Jiangqi
Abstract: Regulation of floral transition and inflorescence development is crucial for plant reproductive success. FLOWERING LOCUS T (FT) is one of the central players in the flowering genetic regulatory network, whereas FLOWERING LOCUS D (FD), an interactor of FT and TERMINAL FLOWER 1 (TFL1), plays significant roles in both floral transition and inflorescence development. Here we show the genetic regulatory networks of floral transition and inflorescence development in Medicago truncatula by characterizing MtFTa1 and MtFDa and their genetic interactions with key inflorescence meristem (IM) regulators. Both MtFTa1 and MtFDa promote flowering; the double mutant mtfda mtfta1 does not proceed to floral transition. RNAseq analysis reveals that a broad range of genes involved in flowering regulation and flower development are up- or downregulated by MtFTa1 and/or MtFDa mutations. Furthermore, mutation of MtFDa also affects the inflorescence architecture. Genetic analyses of MtFDa, MtFTa1, MtTFL1, and MtFULc show that MtFDa is epistatic to MtFULc and MtTFL1 in controlling IM identity. Our results demonstrate that MtFTa1 and MtFDa are major flowering regulators in M. truncatula, and MtFDa is essential both in floral transition and secondary inflorescence development. The study will advance our understanding of the genetic regulation of flowering time and inflorescence development in legumes. Abstract : Double mutation of two flowering genes in Medicago truncatula completely blocks the floral transition, resulting in significantly more biomass compared to wild-type.